RAW MATERIAL INVENTORY PLANNING OF PATIENT MENU USING MATERIAL REQUIREMENT PLANNING (MRP) IN RSIA KENDANGSARI MERR SURABAYA - Dewi Sri (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2021)
Introduction: Material Requirement Planning (MRP) is a technique or a logical procedure to translate the Master Production Schedule (MPS) of the finished goods or end item into the net requirements for some of the components needed to implement the MPS. MRP is used to determine the amount of material needs to support the Master Production Schedule and when the material needs to be scheduled.Methods: The study is conducted on 13 August 2018 until 12 September 2018 at the installation Nutrition RSIA Kendangsari Merr Surabaya. Collecting data in this study using several methods, including: observation- This stage is conducted in all parts related to the object of study, starting from the Purchase Order (PO) by a head cook up to raw material stored in the storage, discussion- author interviews and collects data to communicate and discuss with the respondents. Respondents in this study are the head of the nutrition unit and head cook of RSIA who have the authority doing the purchasing.Results: Planning of procurement of raw materials to the menu rawon in RSIA can use the Exponential Smoothing method. The discussion has compared two methods of forecasting and the results are consistent with the demand’s patterns of Simple Moving Average method, Exponential Smothing. Forecasting has the lowest error rate by using Exponential Smoothing. The second conclusion is a technique of determining the appropriate Material Requirement Planning in raw material procurement to menu rawon in RSIA is using Lot for Lot.